Кинетика восстановления оксида азота (IV) в технологии утилизации систем на основе концентрированной HNO₃ - Гринь, Григорий Иванович; Пономарёв, В. А.; Созонтов, В. И.; Казаков, В. В. (НТУ "ХПИ", 2012)
У статті розглянуто процес відновлення оксиду азоту (IV) одержуваного при віддувці фтороводню в технології утилізації окиснювача рідкого ракетного палива. Наведено дані щодо впливу різних параметрів: часу, температури, типу відновлювача (карбамід, вуглеамонійні солі) на ступінь відновлення NO2 (N2O4). Запропоновані емпіричні рівняння для розрахунку ступеня відновлення для трьох видів відновників.

This article describes the recovery of nitrogen oxide (IV) obtained by the hydrogen fluoride stripping performed in the rocket fuel oxidizer disposition technology. The effect of various parameters, namely, time, temperature, type of reducer (urea, ammonium carbonates) on the degree of NO2 (N2O4) recovery is given. The empirical equations for calculation of the mentioned degree for the three types of reducing agents are provided.
Recovery kinetics of nitrogen oxide (IV) in systems disposition technology based on concentrated HNO₃
Keywords: утилизация систем; процесс утилизации; оксид азота; восстановление